2017
DOI: 10.1038/srep39880
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal measurement and hierarchical classification framework for the prediction of Alzheimer’s disease

Abstract: Accurate prediction of Alzheimer’s disease (AD) is important for the early diagnosis and treatment of this condition. Mild cognitive impairment (MCI) is an early stage of AD. Therefore, patients with MCI who are at high risk of fully developing AD should be identified to accurately predict AD. However, the relationship between brain images and AD is difficult to construct because of the complex characteristics of neuroimaging data. To address this problem, we present a longitudinal measurement of MCI brain ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…Huang et al used longitudinal changes over 4 years of T1-weighted MRI scans to predict AD conversion in MCI subjects. Their results showed that the model with longitudinal data consistently outperformed the model with baseline data, especially achieved 17% higher sensitivity than the model with baseline data (Huang et al, 2017 ). In our study, the results showed that the longitudinal features failed to provide additional information for identifying aMCI and naMCI compared with cross-sectional features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Huang et al used longitudinal changes over 4 years of T1-weighted MRI scans to predict AD conversion in MCI subjects. Their results showed that the model with longitudinal data consistently outperformed the model with baseline data, especially achieved 17% higher sensitivity than the model with baseline data (Huang et al, 2017 ). In our study, the results showed that the longitudinal features failed to provide additional information for identifying aMCI and naMCI compared with cross-sectional features.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al presented a longitudinal measurement of MCI brain images and a hierarchical classification method for AD prediction. Their method using longitudinal data consistently outperformed the method using baseline data only (Huang et al, 2017 ). Despite these efforts, employing machine learning technique with longitudinal MRI features for MCI subtypes classification is rarely studied.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…follow-up patient visits), in an effort to improve long-term prognosis. However, this is a challenging task requiring longitudinally consistent feature selection and mitigation of missing timepoints [ 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Table shows that the nested LOOCV method can select the optimal feature dimension for different between‐group comparisons and receives the best classification performance in this dimension. The accuracy rates obtained by the classification method and the feature combination strategy are all higher than those of previous studies . The accuracies, sensitivities, specificities, PPVs, NPVs and AUCs have been greatly improved after the combination of longitudinal time points (ie, bl + 12 m and bl + 12 m + 24 m).…”
Section: Discussionmentioning
confidence: 69%